KONSEP PENGUNAAN FILSAFAT PENDIDIKAN DALAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH - Novialdi Novialdi (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2023)
Very good learning requires careful planning, careful planning needs to think deeply about the teaching process in accordance with the plan, so that the teaching and learning process can be achieved optimally as planned. Education is very influential on the people closest to the child's life, the family environment has a very large influence on the growth and development of children's intelligence. The learning principles of Private Islamic Madrasahs are goal-oriented, activity, individuality, integrity, interactive, inspiring, fun, challenging, motivational. Meanwhile, models of child-centered learning approaches are: the Montesori approach, the Street bank approach, the High Scope approach, the Creative curriculum approach, and the Regio Emillia approach.